2010
DOI: 10.1007/s00330-010-1734-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of diffusion-weighted magnetic resonance imaging during chemoradiotherapy for head and neck squamous cell carcinoma

Abstract: DWI during CRT for HNC allows more accurate response prediction than anatomical imaging, correlating significantly with 2-year LRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
160
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(180 citation statements)
references
References 39 publications
15
160
2
3
Order By: Relevance
“…In addition to the increasing understanding of its capability to depict physiological and functional changes in salivary glands after RT, it has also proven to be a promising tool for tissue characterization, nodal staging and early response evaluation in this patient group [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increasing understanding of its capability to depict physiological and functional changes in salivary glands after RT, it has also proven to be a promising tool for tissue characterization, nodal staging and early response evaluation in this patient group [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Vandecaveye et al14 reported that ΔADC in primary tumors and nodal metastases, 2 and 4 weeks after the start of chemo‐radiation therapy, were significantly lower in lesions with post‐TX recurrence than in lesions with CR for primary tumors, relative to nodal metastases. Also, King et al13 reported a significant correlation between local failure and post‐TX ADC, but not pre‐ or intra‐TX ADC values.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that the quantitative imaging metric apparent diffusion coefficient (ADC), derived from DW‐MRI data using a minimum of two b (b = diffusion‐weighted gradient factor) values, has shown promise in clinical applications ranging from tumor characterization to the evaluation of treatment response 10, 11, 12. It has been reported that hypercellular tissue is characterized by low ADC, whereas hypocellular tissue with necrosis, or apoptosis, is characterized by high ADC; the change in ADC (ΔADC) before, during, or after chemoradiation therapy in HNSCC is a surrogate biomarker of treatment response 13, 14…”
mentioning
confidence: 99%
“…King et al [3] and Vandecaveye et al [4] stressed the necessity of an early identification of non-responders to radiotherapy or chemoradiotherapy for modification or change of treatment regimens in patients with head and neck squamous cell carcinoma. In this early post-treatment phase previous radiological assessment has been described as suboptimal: Treatmentinduced inflammation may hamper the accuracy of PET-CT. Volumetric analysis with anatomical imaging (CT, MRI) has shown variable results.…”
Section: Introductionmentioning
confidence: 99%
“…Among others this principle is used for the prediction and monitoring of treatment response in malignancies undergoing a non-surgical therapy. King et al [3] and Vandecaveye et al [4] analysed whether a change in ADC could be an early diagnostic biomarker to solve the problematic evaluation of residual tissue in the tumour and lymph node bed. Vandecaveye et al [4] examined 30 patients before, and at the 2nd and 4th week during radiochemotherapy by anatomical MRI and DWI and studied changes in tumour volume and ADC.…”
Section: Introductionmentioning
confidence: 99%